Zero Waste Management of Casual Dining Restaurants in Baguio City and La Trinidad Benguet: Basis for a Sustainable Waste Management Framework - Lumague, Rudolfo Jr (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed zero-waste lifestyle implementation, green practices, and pro-environmental behaviors among selected casual restaurants in Baguio City and La Trinidad, Benguet as basis for strengthening sustainable waste management practices. It was anchored on Johnson’s 5Rs framework, Stern’s Environmentally Significant Behavior, and Elkington’s Three Pillars of Tourism Sustainability. The study used a mixed-method approach with descriptive, correlational, and thematic analysis procedures. Data were gathered from 262 respondents composed of restaurant managers, employees, and customers through a researcher-made questionnaire and semi-structured interviews. The questionnaire measured zero-waste practices in terms of refuse, reduce, reuse, recycle, and rot; green practices in terms of green product use, solid waste management, and energy efficiency; and pro-environmental behaviors in terms of attitude, subjective norms, and perceived behavioral control. Findings showed that refuse, reduce, and rot practices were generally implemented at a medium priority level, reuse practices were mostly invested in, while recycling showed weak overall prioritization. Green product use was practiced at a medium priority level, while solid waste management was considered a high priority. Respondents demonstrated strong pro-environmental attitudes, subjective norms, and perceived behavioral control. Customer results showed support for sustainable sourcing, reuse, recycling, composting, and visible green practices. Statistical findings indicated a significant difference in green practices based on zero-waste lifestyle implementation, while no significant relationship was found between zero-waste implementation and managers’ pro-environmental behaviors. The study concluded that zero-waste management practices are linked to green practices and customer sustainability behavior, but improvements are needed in staff training, waste segregation, recycling, composting, and consistent implementation. The study supports SDG 12, with links to SDGs 3, 6, 8, 11, 13, 14, and 17 through waste reduction, public health protection, resource conservation, responsible business operations, and stakeholder cooperation. Its sustainability impact lies in promoting environmental conservation, institutional compliance, cost reduction, customer awareness, and community-based sustainable restaurant operations.
Keywords: Baguio City; Casual Restaurants; Green Practices; La Trinidad; Pro-Environmental Behavior; Solid Waste Management; Sustainable Restaurant Operations; Zero-Waste Lifestyle